Antityrosinase activity and photosynthetic pigments in seaweed treated sprouts of Vigna aconitifolia - NIDHI VERMA; KRISHAN D SEHRAWAT; SANGEETA KUMARI; ANITA R (The Indian Journal of Agricultural Sciences, 2019)
The seaweed, Ascophyullum nodosum is the focus of the research these days and is looked upon as an important alternative bio-fertilizer. For this purpose the interaction of the seaweed with different plants including legumes is important to understand. We previously noticed lesser pigmented nodules in legume plant Vigna aconitifolia, when grown in presence of A. nodosum Extract (ANE). We therefore studied the effect of the ANE on the tyrosinase inhibition activity, an enzyme known to produce melanin pigment. In addition, the effect of the treatment of ANE on the photosynthetic pigments was also recorded. The seeds of Vigna aconitifolia were treated with 0%, 0.01%, 0.05%, 0.10%, 0.50% and 1.0% of A. nodosum extract for different time periods from 0–24 hours. It was observed that with the increased exposure to the seaweed (ANE), the tyrosinase inhibition activity also increased up to 0.05% of the seaweed concentration at 24 h of soaking and decreased after increasing the concentration of ANE from 0.1–1.0% at the same time period. Seed treatment with 0.05% seaweed was found to be the most effective concentration showing highest tyrosinase inhibition.